The Influence of Brand Trust and Customer Satisfaction on Customer Loyalty Among Shopee Users in Rural Area - Ali, Muhammad Rivaldo; Kartawan; Santosa, Allicia Deana (Jurnal Multidisiplin Madani, 2024)
The study focuses on the impact of brand trust and User Satisfaction on Customer Loyalty among Shopee users in Tasikmalaya Regency Indonesia. It employs a survey method and structural equation modeling (SEM) with mediation analysis to investigate the relationships between these key constructs. The research objectives are to explore the impact of brand trust on customer satisfaction and customer loyalty, as well as the influence of customer satisfaction on customer loyalty. The study's findings are expected to contribute to both theoretical understanding and practical strategies for e-commerce companies, particularly Shopee, to enhance their business performance in a highly competitive market. The study utilizes non-probability sampling with a purposive sampling method and collected 250 respondents Shopee Users. The data analysis includes descriptive statistics to assess customer perceptions and confirmatory factor analysis to evaluate the unidimensionality of the measurement constructs. The study's results are expected to provide valuable insights into the factors influencing customer loyalty in the e-commerce context, specifically focusing on Shopee users in Tasikmalaya offer practical implications for businesses in the industry